Inside Back Cover: Reversible Supramolecular Surface Attachment of Enzyme–Polymer Conjugates for the Design of Biocatalytic Filtration Membranes (Angew. Chem. Int. Ed. 49/2015). Issue 49 (26th October 2015) - Moridi, Negar; Corvini, Philippe F.‐X.; Shahgaldian, Patrick
Abstract : Haute couture supramolecular modification of polymeric filtration membranes allows the stable yet reversible immobilization of tailor‐made biocatalysts on the membrane surface. The chemical strategy described in the Communication by P. Shahgaldian et al. on page 14800 is based on multiple‐point interactions between the membrane surface on which cyclodextrins have been immobilized and a soluble enzyme–polymer conjugate containing adamatane units.